The Development of Liveworksheet-Assisted Electronic Student Worksheets (E-LKPD) for Fourth Grade English Learning at SDN 13 Sitiung - Lutfiah, Zumrotun; Ningsih , Sri Yunimar; Oktafia, Mira Cornellia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is based on a problem observed in the learning process, namely the lack of student enthusiasm in completing student worksheets (LKPD). The purpose of this study is to develop an E-LKPD supported by Liveworksheets for Chapter 4 of the English subject for fourth-grade students, aimed at producing a valid, practical, and effective E-LKPD that can improve student learning outcomes at SDN 13 Sitiung. The development model used is the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The validation results of the E-LKPD, evaluated by five validators (graphics expert, content expert, language expert, assessment expert, and instructional module expert), yielded an average score of 86.8%, categorized as “highly valid,” indicating that the E-LKPD is suitable for use. The practicality results, assessed by a fourth-grade teacher and students, showed scores of 89.0% and 95.7% respectively, both falling into the “highly practical” category, suggesting that the E-LKPD is easy to use during the learning process. The effectiveness test results, based on a learning outcome test, showed that 85% of students achieved mastery, categorized as “highly effective,” indicating success in achieving the intended learning objectives.